2016
DOI: 10.1007/s00405-016-4263-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic ethmoidectomy performed on a day-case basis: a prospective bi-centric study

Abstract: Evaluation of endoscopic ethmoidectomy performed as a day-case in terms of security, quality, and satisfaction of the patient. This prospective observatory bi-centric study over 1 year included 74 patients undergoing an ethmoidectomy respecting the eligibility criteria of ambulatory care. We recorded patients' demographic data, operative details, satisfaction, postoperative course, and follow-up results. Nasal symptoms were evaluated by SNOT-22 on preoperative appointment and postoperatively at D30. No non-abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A French study focussing on patient reported outcomes for day‐case endoscopic ethmoidectomy reported no readmission and no major complications in their series of 74 patients. SNOT‐22 scores decreased on average by 56% post‐operatively, demonstrating good surgical outcomes in day‐case ESS 26 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A French study focussing on patient reported outcomes for day‐case endoscopic ethmoidectomy reported no readmission and no major complications in their series of 74 patients. SNOT‐22 scores decreased on average by 56% post‐operatively, demonstrating good surgical outcomes in day‐case ESS 26 …”
Section: Discussionmentioning
confidence: 84%
“…SNOT-22 scores decreased on average by 56% post-operatively, demonstrating good surgical outcomes in day-case ESS. 26 One of the reasons often cited for the need to have an overnight observation following ESS, other than patient co-morbidities, is the risk of post-operative haemorrhage. 19 However, advances in ESS techniques have led to reduced morbidity associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Further carbon savings could be made by reducing variation between hospitals in day-case delivery. Minimising hospital stays while maintaining levels of care and patient outcomes is one way to reduce carbon emissions, and there is evidence that day-case and outpatient surgery is as safe and effective as inpatient surgery for many procedures across a range of specialties [11] , [22] , [23] , [24] , [25] .…”
Section: Discussionmentioning
confidence: 99%
“…SNOT-22 scores decreased on average by 56% post-operatively, demonstrating good surgical outcomes in day-case ESS. 16 One of the reasons often cited for the need to have an overnight observation following ESS, other than patient co-morbidities, is the risk of post-operative haemorrhage. 12 However, advances in ESS techniques have led to reduced morbidity associated with the procedure.…”
Section: Discussionmentioning
confidence: 99%